TranscribEase – Speech and Document Summarizer - S, Nisarga; Devangavi, Arpitha; Otageri, Prerana M; N, Prarthana (Journal of Innovative Image Processing, 2024)
This research introduces a summarization app using Flask and Hugging Face API. It summarizes audio, PDFs, and text efficiently. It features robust audio summarization by converting speech to text and then summarizing it. It also supports PDF and text summarization. The pre-trained NLP models like DistilBART, offers accurate and concise summaries. The user interface is intuitive, allowing seamless interaction. Overall, it’s a comprehensive tool for extracting insights from various content sources, enhancing productivity.